2020
DOI: 10.1186/s12888-020-02550-y
|View full text |Cite
|
Sign up to set email alerts
|

Post traumatic stress symptom variation associated with sleep characteristics

Abstract: Background: Post traumatic stress disorder (PTSD) and sleep problems are highly related. The relationship between nighttime sleep characteristics and next day post traumatic stress symptoms (PTSS) is not well known. This study examined the relationship between the previous night's sleep duration, number of awakenings, sleep quality, trouble falling asleep, and difficulty staying asleep and PTSS the following day. Methods: Using an ecological momentary assessment methodology, individuals with probable PTSD (N =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 50 publications
3
25
0
Order By: Relevance
“…However, those with PTSD reported significantly more frequent difficulty staying asleep (32% of nights versus 16% of nights among those without PTSD). Prior research has shown that difficulty staying asleep was the strongest predictor of next day's post traumatic stress symptoms [10]. These data therefore suggest that better understanding the greater frequency of difficulty staying asleep, rather than its temporal pattern may aid in understanding its relationship to next day's post traumatic stress symptoms.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…However, those with PTSD reported significantly more frequent difficulty staying asleep (32% of nights versus 16% of nights among those without PTSD). Prior research has shown that difficulty staying asleep was the strongest predictor of next day's post traumatic stress symptoms [10]. These data therefore suggest that better understanding the greater frequency of difficulty staying asleep, rather than its temporal pattern may aid in understanding its relationship to next day's post traumatic stress symptoms.…”
Section: Discussionmentioning
confidence: 74%
“…Sleep quality varied across the 7 days of the week and was better on weekends than weekdays, but only among those with PTSD. Sleep quality is closely related to the other sleep characteristics [10]. The specific weekday versus weekend difference among those with PTSD may therefore suggest that PTSD-related stressors (such as threat cues) may be more common during weekdays or, alternatively, protective factors such as social support may be more present on weekends.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations